Care in knowledge creation - Von Krogh, Georg (California management review)
Knowledge creation is the key source of innovation in any company. However, it is a fragile process fraught with uncertainty and conflict of interest. The effective creation of new knowledge (especially tacit social knowledge) hinges on strong caring among organization members. Managers have several means to facilitate caring relations, including new incentive systems, mentoring programs, care as an articulated value, project debriefings, and training programs in care-based behavior.